Strategic change and culture management in organisation development - Abdul Rahman, Shukran (2019)
This paper aims to develop participants’ understanding on the scope of organization strategic change and the scope of Culture Management. It discusses the steps to create effective culture in organization; and the scope and the development of learning organization. Besides, the paper also discusses the initiatives to build knowledge management; and illustrate a case study and sample for the implementation of (a) effective culture; (b) learning organization; and (c) knowledge management